Stylistic features of dialectisms in Turkish folk songs - Muminova , Nilufar Toshpulat qizi (The Lingua Spectrum, 2026)
This article analyzes the stylistic features of dialectisms found in the language of Turkish folk songs. It highlights that dialectisms, as an integral part of the national language, perform important functional roles in literary texts. Using examples from Turkish folk songs, phonetic, grammatical, and lexical dialectisms are examined and analyzed.